Value of Gamma-Glutamyl Transpeptidase for Diagnosis of Biliary Atresia by Correlation With Age. Issue 3 (September 2016) - Chen, Xiaoli; Dong, Rui; Shen, Zhen; Yan, Weili; Zheng, Shan
ABSTRACT: Objectives: The aim of the study was to analyze the value of gamma-glutamyl transpeptidase (GGT) for distinguishing biliary atresia (BA) from non-BA for patients suspected of having neonatal obstructive jaundice by correlation with age. Methods: From January 2003 to March 2014, cholangiography and/or surgical exploration were undertaken in 1469 patients with suspicion of having neonatal obstructive jaundice. A total of 1338 patients were diagnosed with BA intraoperatively. Preoperative medical records were compared between BA and non-BA patients. Results: Preoperative levels of total bilirubin, direct bilirubin, and GGT were significantly higher in the BA group ( P  < 0.05), whereas the non-BA group had higher alkaline phosphatase levels ( P  = 0.0003). The area under the receiver operating characteristic curve of total bilirubin, direct bilirubin, GGT, and alkaline phosphatase was 0.584, 0.614, 0.843, and 0.398, respectively. In all age groups (i: 31–60 days; ii: 61–90 days; iii: 91–120 days; iv: ≥121 days), BA groups had higher GGT levels (in IU/L) (i: 725.3 ± 549.9; ii: 927.0 ± 679.8; iii: 1114.3 ± 823.1; iv: 767.5 ± 666.7). The level of GGT in patients with BA younger than 30 days was 834.2 ± 475.3 IU/L. GGT levels had the highest diagnostic value (0.869) in group ii (61–90 days) and the lowest diagnosis value (0.712) in group iv (≥121 days). At a cutoff of >303 IU/L in group ii (61–90 days), GGT had 82.8% sensitivity and 81.6% specificity for the discrimination of BA. Conclusions: GGT levels contribute to the diagnosis of BA before 120 days. Age must be considered if using GGT levels as a diagnostic test for BA.